Soybean breeding in southwestern China improved P and N utilization efficiencies by increasing phosphorus and nitrogen partitioning to pods - Luo, Xin; Dong, Rui; Siddique, Kadambot H. M.; He, Jin; Jin, Yi (Frontiers in Sustainable Food Systems, 2023)
Introduction Soybean breeding in southwestern China has vastly improved soybean yields with the increasing demand for nutrients such as phosphorus (P) and nitrogen (N). This study aimed to assess the impact of soybean breeding on P and N utilization efficiencies. Methods Field experiments with split-plot experimental designs were conducted at two locations [Dafang (DF) and Shiqian (SQ)] in the 2019 growing season to determine the agronomic efficiency of P fertilizer (AEp), P and N utilization efficiencies, and P and N accumulation and partitioning in different soybean organs under 0 (P0) and 35 (P35) kg ha−1 P supply. Results The results showed that soybean breeding targeting high seed yield also improved AEp (p < 0.05) and P (p < 0.05) and N utilization efficiencies (p < 0.05), with the improvement in AEp associated with the high yield response to P supply. P and N accumulation significantly increased in pods (p < 0.05) and leaves (p < 0.05) but not in stems or roots with year of release, while P and N concentrations did not change in any organ with year of release. In addition, only pod dry weight significantly increased (p < 0.01) with year of release, and P and N partitioning increased to pods (p < 0.05) but decreased to stems (p < 0.05) with year of release. Correlation and PCA analyses revealed P and N utilization efficiencies positively correlated with P and N partitioning to pods but negatively correlated with P and N partitioning to stems. While P supply increased P and N accumulation, it reduced P utilization efficiency. Discussion We conclude that (1) soybean breeding improved AEp and P and N utilization efficiencies; (2) the increased P and N partitioning to pods but decreased partitioning to stems contributed to the high P and N utilization efficiencies in new soybean cultivars, reducing the demand for N and P; (3) P supply increased nutrient accumulation but reduced P utilization efficiency. These results highlight the significance of appropriate resource allocation among organs and efficient P management for enhancing nutrient utilization and reducing fertilizer requirements.